Determination of water balance equation components in irrigated agricultural watersheds using SWAT and MODFLOW models : A case study of Samalqan plain in Iran - Shima Nasiri; Hossein Ansari; Ali Naghi Ziaei (Journal of Groundwater Science and Engineering, 2022)
Increasing water demands, especially in arid and semi-arid regions, continuously exacerbate groundwater as the only reliable water resources in these regions. Samalqan watershed, Iran, is a groundwater-based irrigation watershed, so that increased aquifer extraction, has caused serious groundwater depletion. So that the catchment consists of surface water, the management of these resources is essential in order to increase the groundwater recharge. Due to the existence of rivers, the low thickness of the alluvial sediments, groundwater level fluctuations and high uncertainty in the calculation of hydrodynamic coefficients in the watershed, the SWAT and MODFLOW models were used to assess the impact of irrigation return flow on groundwater recharge and the hydrological components of the basin. For this purpose, the irrigation operation tool in the SWAT model was utilized to determine the fixed amounts and time of irrigation for each HRU (Hydrological Response Unit) on the specified day. Since the study area has pressing challenges related to water deficit and sparsely gauged, therefore, this investigation looks actual for regional scale analysis. Model evaluation criteria, RMSE and NRMSE for the simulated groundwater level were 1.8 m and 1.1% respectively. Also, the simulation of surface water flow at the basin outlet, provided satisfactory prediction (R2=0.92, NSE=0.85). Results showed that, the irrigation has affected the surface and groundwater interactions in the watershed, where agriculture heavily depends on irrigation. Annually 11.64 Mm3 water entered to the aquifer by surface recharge (precipitation, irrigation), transmission loss from river and recharge wells 5.8 Mm3 and ground water boundary flow (annually 20.5 Mm3). Water output in the watershed included ground water extraction and groundwater return flow (annually 46.4 Mm3) and ground water boundary flow (annually 0.68 Mm3). Overally, the groundwater storage has decreased by 9.14 Mm3 annually in Samalqan aquifer. This method can be applied to simulate the effects of surface water fluxes to groundwater recharge and river-aquifer interaction for areas with stressed aquifers where interaction between surface and groundwater cannot be easily assessed.